Meta-analysis of the relationship between teachers' self-efficacy and attitudes toward inclusive education. (January 2022) - Yada, Akie; Leskinen, Markku; Savolainen, Hannu; Schwab, Susanne
Abstract: This meta-study aims to examine the size of the relationship between teachers' self-efficacy and attitudes toward inclusive education of K-12 students with special educational needs and to identify potential moderators (publication, sample, and research procedure characteristics). We synthesized the research conducted from 1994 to 2018, and 41 studies were included. Bare-bones meta-analysis with random effect model revealed a sample size weighted correlation coefficient between teachers' self-efficacy and attitudes as r ¯  = 0.35 ( CI  = 0.31-0.39). The between-study variations were not associated with hypothesized publication and sample characteristics. However, the self-efficacy measurement method accounted for a statistically significant strength of association. Highlights: A meta-analysis was used to examine relationship between teachers' attitudes and self-efficacy in inclusion. Effects of 43 unique samples of in-service teachers are aggregated. Meta-analyses reveal a positive sample size weighted correlation between teachers' self-efficacy and attitudes. Findings suggest the relationship might be somewhat universal regardless of time, culture, or gender. Implications for teacher training and future research directions are discussed.